Association of right bundle branch block or intraventricular conduction delay with recurrence of atrial fibrillation after catheter ablation - Sung Ho Lee; Ji‐Hoon Choi; Seung‐Jung Park; Kyoung‐Min Park; June Soo Kim; Young Keun On (Annals of Noninvasive Electrocardiology, 2023)
Abstract Background The association between bundle branch block (BBB) and recurrence of atrial fibrillation (AF) after catheter ablation is unclear. The aim of this study was to determine whether AF combined with BBB is associated with AF recurrence after catheter ablation. Methods A total of 477 consecutive AF patients who underwent catheter ablation were included. The AF patients were divided into three groups according to BBB: AF without BBB (n = 427), AF with right bundle branch block (AF with RBBB) (n = 16), and AF with intraventricular conduction delay (AF with IVCD) (n = 34). Results Of the 477 AF patients (mean age 57 years, 81% men, median CHA2DS2‐VASc score of 1), 16 (3.4%) patients had RBBB, and 34 (7.1%) patients had IVCD. During a mean follow‐up of 15.2 ± 6.7 months, 119 patients (24.9%) had recurrence of AF. Of these, 111 (26%) patients were in the AF without BBB group, with 2 (12.5%) and 6 (17.6%) patients in the RBBB and IVCD groups, respectively. The Kaplan–Meier estimate of the rate of recurrent AF was not significantly different among the three groups (p = .39). Multivariable analysis showed that persistent AF (HR 1.7, 95% CI 1.15–2.50, p = .007), chronic kidney disease (HR 2.94, 95% CI 1.20–7.17, p = .01), and left atrial diameter (HR 1.04, 95% CI 1.009–1.082, p = .01) were significantly associated with AF recurrence. Conclusion AF with BBB was not significantly associated with the recurrence of AF after catheter ablation in middle‐aged patients with low‐risk cardiovascular profile.